Amazônia azul e a proteção do ambiente na Plataforma Continental - Quirino, Larissa Retamar Corrales (2020)
Brazil is one of the largest oil producers in the world mainly in the area of the “Amazônia Azul” which is a vast maritime area on the Brazilian Atlantic coast. Economic investments for the development of the sector increase significantly every year, the environmental impacts of offshore oil extraction proportionally also increase, thus being entitled to a deeper analysis of the Brazilian government's efforts to maintain the environmental and economic balance of the “Amazônia Azul”. In 2011, the multinational oil company Chevron caused a major hydrocarbon leak in an area of Brazilian sovereignty. With the scope of this accident, this work analyzes the international and national legislation and verifies if they were properly applied to the specific case.